TRATADOS DE LIBRE COMERCIO Y LOS IMPACTOS ECONÓMICOS - SOCIALES - López Mas, Julio (2006)
The current article tries to describe and to explain the main social and economic impacts distinguishing the peruvian economic structure, in its character of exporting primary economy, the great and medium business as the small business, to those whom the impact of tariff measures affects in at least two aspects. Different points of view in the high-priority themes of agenda are discussed so that the benefits of these and other trade agreements are not absorbed for a fraction of the population, but by the majority.